Moderation of Self-Regulatory Efficacy between Leader-Member Exchange and Procedural Justice on Workplace Deviance Behavior at Perum BULOG West Java Region - Eka Frasani, Oktaviany; Gunawan, Asep; Priyono, Dadang (Jurnal Ekuisci, 2024)
This study analyzes whether self-regulatory efficacy moderates the correlation between leader-member exchange and procedural justice on workplace deviance behavior. Based on resource allocation theory and cognitive social theory, this study examines the effects of self-regulatory efficacy of leader-member exchange and procedural justice on the deviant behavior of 155 employees at Perum BULOG, West Java Region. Researchers did not find a significant correlation between leader-member exchange and workplace deviance behavior. Similarly, the results show that procedural justice does not correlate with workplace deviance behavior. The researchers also did not find that self-regulatory efficacy could moderate the correlation between leader-member exchange and workplace deviance behavior. However, self-regulatory efficacy can moderate the correlation between procedural justice and workplace deviance behavior. Data collection in this study used a questionnaire distributed by google form. Data analysis in this study used Structural Equation Modeling (SEM) with the WarpPLS approach.